The Use of APE “Numtrack” to Teach Students in Numeracy: A Case Study at ICC Al Anshar Bahau, Malaysia - Bela Millatin Nadzifah; Rini Listyowati; Anisa Anisa (Action Research Journal Indonesia (ARJI), 2025)
This study examines the use of APE Numtrack to improve students' numeracy skills, particularly in environments with limited technological access and a shortage of qualified teachers. The study is motivated by the observation that many students struggle with basic numeracy due to inadequate instructional resources and learning tools. Conducted at ICC Al-Anshar, Bahau, Malaysia, this study employs a qualitative method with a case study approach. The informants include teachers and students who directly engage with APE Numtrack in their learning process. Data were collected through classroom observations and semi-structured interviews and analyzed thematically to identify recurring patterns and insights. The findings indicate that APE Numtrack significantly enhances students' understanding of basic numeracy by providing interactive and personalized feedback, making learning more engaging. However, some challenges were identified, particularly regarding the durability and functionality of the tool. The study implies that while APE Numtrack is an effective learning aid for foundational numeracy skills, its application remains limited for more complex mathematical concepts. Based on these findings, future research is recommended to explore ways to improve APE Numtrack's durability and expand its functions to accommodate advanced mathematical content, ensuring its broader usability in various educational settings.